ISOLASI, IDENTIFIKASI DAN UJI POTENSI BAKTERI YANG BERPERAN PADA PENGOLAHAN AIR LIMBAH YANG MENGANDUNG RHODAMIN B DALAM BIOSISTEM TANAMAN - Sri Satya Laksmi Utari, Sang Ayu; Darmayasa, Ida Bagus Gede; Budiarsa Suyasa, I Wayan (SIMBIOSIS; Vol 3 No 1 (2015), 2015)
Rhodamin B is a dangerous synthetic dyes substances used as a fabric dye in the textile industry. Biodegradation is one way that is used in the processing of liquid waste Rhodamin B. Biodegradation technique is leveraging the ability of microbial activities degrade or eliminate pollutant compounds. The main objective of this research was to investigate the characteristic of bacteria that are capable of living on wastewater containing Rhodamin B and the effectiveness of single and microbial consortium isolates to degrade Rhodamin B on wastewater. The isolation of the bacteria was done by plating method and the identification of the bacteria by using a Kit API 20E. Test of bacterial potential of Rhodamin B dyes substance carried out in the Microbiology Laboratory, Biology Department, Faculty of Science, Udayana University. It was found in this research that five bacterial isolates were obtained (Pseudomonas sp., Shigella spp., Stenotrophomonas sp., Pasteurella sp. dan Proteus sp.). Pasteurella sp. had the highest percentage degrade effectiveness of 40.55%. Microbial potential degrade Rhodamin B by Pasteurella sp. dan Proteus sp. results showed significant differences (P <0.05) to control. Keyword: bacteria, biodegradation, Rhodamin B